Análise da resposta em banda estreita de um canal marítimo na faixa de 3,5 Ghz - Vieira, Pedro Armando (2010)
This work aims to present the result of narrowband measurements carried out in the year of 2009 in maritime mobile radio channel, in the coast region of Macaé city, base to maritime operations in the Campos' Basin oil bearing, Rio de Janeiro state. With the results obtained a comparative analysis was done with the two-ray model and the attenuation factor was calculated. The results of an extensive study of the slow and fast signal variability to allow a better characterization of the mobile maritime radio channel are also presented. The fast variability was analyzed comparing the Rayleigh, Rice and Gauss distributions, considering 20 λ sectors. The level crossing rate and average fading duration were determined as well. At the end, it was analyzed the slow signal variability behavior and a correction factor was proposed in way to improve the calculation of path loss prediction due to observed conditions of the sea by using Beaufort scale.